Karakteristik Individu Dan Kondisi Lingkungan Pemukiman di Daerah Endemis Leptospirosis Di Kota Semarang - Tri Ramadhan; Bambang Yunianto (ASPIRATOR - Journal of Vector-borne Disease Studies, 2010)
Leptospirosis is an acute febrile illness infecting human and animal (zoonosis) and caused by the bacteria leptospira. Semarang city is one endemic leptospirosis with incidence rate in 2009 of 13,27/100.000 and case fatality rate 3,5%. This study aimed to know the epidemiological characteristics of leptospirosis cases and the relationship of environmental conditions of settlement with the incidence of leptospirosisThe study was observational with cross sectional design. Data population are the people who visit the health center with clinical symptoms of leptospirosis and secondary data from the Health Department of Semarang. Sample are people who visited the health center with clinical symptoms of leptospirosis (mainly: fever (body temperature> 37oC) or fever accompaniedby headache, muscle aches, conjunctivitis and rash). Data environmental conditions of settlement had beed observed and interviewed using, and analysed bivariat with chisquare. The results show characteristics of respondents most of the age group 10 -19 years(38.1%), male sex (56.2%), education level did not complete primary school (30.5%) Distributioncases of leptospirosis attack more men (55%) with mortality rate (CFR = 3.6), and in the age group 0-19 years that is as much as 32.5% (CFR=14.29)Environmental conditions associated with the occurrence of leptospirosis include kitchen wall not a wall, no plavond, open dumping and dirty house. To prevention transmission of leptospirosis, among others, hygiene sanitasi,rat proofing so it does not make to nest rat.